Gas Tungsten Arc Welding of Cu-Al-Mn Shape Memory Alloys - Crispim, Beatriz Prego Lopes (2018)
Recently, applications using shape memory alloys (SMAs) have been attracting interest, due to their unique properties. Their application extends to a wide variety of fields, such as automotive, aerospace, biomedical and civil engineering industries. Among the existing classes of shape memory alloys, NiTi is the most studied one. However, Cu-based SMAs are emerging as potential substitutes of NiTi, due to their lower cost and potential for application in damping devices. The development of joining technologies is of major interest, because it allows the growth of potential applications of any engineering alloy. Thus, the necessity of studying the joining of SMAs without compromising their properties. This study focused on the production of similar Cu-Al-Mn joints by gas tungsten arc welding. The microstructure and tensile properties were evaluated to understand the effects of welding on the microstructural and mechanical properties of the welded joints. The superelastic Cu-Al-Mn presented good weldability and no significant changes of the overall tensile properties of the welded specimens were observed, when compared to the base material. This is the first reported study regarding the effects of welding on Cu-based shape memory alloys, using an arc-based source.